Advances in Information Systems Development AI for IS Development and Operations - Silaghi, Gheorghe Cosmin; Buchmann, Robert Andrei; Niculescu, Virginia; Czibula, Gabriela; Barry, Chris; Lang, Michael; Linger, Henry; Schneider, Christoph (Cham : Springer International Publishing : Imprint: Springer, 2023)
This volume is a collection of papers on emerging concepts, significant insights, and novel approaches on information systems development (ISD). It examines and investigates up-and-coming trends in ISD in general, emphasizing benefits and risks of Artificial Intelligence in the development and operation of Information Systems. The book draws on invited papers selected from the proceedings of the 30th International Conference on Information Systems Development hosted by Babeș-Bolyai University, Cluj-Napoca, Romania, August 31 - September 2, 2022 (ISD2022). The theme of ISD2022 was "Artificial Intelligence for Information Systems Development and Operations". The conference focused on the interplay between Information Systems and Artificial Intelligence, trying to emphasize novel, smarter automation approaches and the mitigation of risks related to AI adoption. Primary readership of the volume are researchers interested in methodological and operational perspectives related to ISDin general, and to AI adoption as a means of digital transformation in particular.
A DSR study on Iterative Tool Development to Measure IT Process Maturity in an Agile Context -- A living lab perspective on information systems development process -- Cloud-based Business Intelligence Solutions in the Management of Polish Companies -- Conceptualizing Node.js Projects: a Graph-oriented Technology-specific Modeling Method -- Employing Graph Databases for Business Process Management and Representation -- IT Alignment as a Roadmap for Digital Transformation Success.
Keywords: Business information services; Electronic data processing -- Management; Application software; Database management; Business Information Systems; IT Operations; Computer and Information Systems Applications; Database Management System